Analysis Of Earthquake Fault Type In 2022 in the Mentawai Region Using Waveform Inversion Method - Ika Sri Fahmi; Syafriani Syafriani; Hamdi Hamdi; Letmi Dwiridal (Department of Physics, Universitas Negeri Padang, 2023)
Indonesia is a country prone to earthquake disasters, because Indonesia is located in the collision area between plates, and one of the areas in Indonesia where plate movements often occur is Mentawai. Analysis of waveform data on the 2022 earthquake in the Mentawai region was carried out to determine the type of fault. The data used in this research is local seismic data downloaded from webdc.eu. Seismic data was analyzed using waveform inversion method implemented in ISOLA program. In the ISOLA program, data processing is carried out which includes: inputting 3-component seismic data, earthquake info events, selecting stations, green functions, performing inversion, and displaying results in the form of tensor moment values, strike, dip, and rake values. From the data analysis, the moment tensor value is obtained with the range of each component of M11 is -8.348 to -3.673, M22 is 0.710 to -2.037, M33 is 7.639 to 5.710, M31 is 2.050 to 3.761, M32 is 3.484 to -5.672, M12 is -2.751 to 2.455. Then the inversion results obtained in the form of fault parameters, namely strike, dip, and rake for two nodals that will be analyzed to determine the fault plane. Based on the moment tensor value, it is found that the type of earthquake fault in 2022 in Mentawai region is dominated by reverse fault and oblique fault patterns.